2021
DOI: 10.2196/29084
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and Cardiovascular Health Effects of e-Cigarette Substitution: Protocol for Two Living Systematic Reviews

Abstract: Background Despite the clear risks of tobacco use, millions of people continue to smoke. Electronic nicotine delivery systems (ENDS), commonly called e-cigarettes, have been proposed as a substitute for those who are unwilling or unable to quit. Current systematic and narrative reviews on the health effects of ENDS use, particularly respiratory and cardiovascular effects, have come to differing conclusions. Objective We conducted two systematic reviews … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Our review conforms to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) 2020 guidelines [ 19 ], see Online Resource 1 PRISMA 2020 Checklist. The protocol was registered with PROSPERO #CRD42021239094 and published in a peer-reviewed journal [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review conforms to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) 2020 guidelines [ 19 ], see Online Resource 1 PRISMA 2020 Checklist. The protocol was registered with PROSPERO #CRD42021239094 and published in a peer-reviewed journal [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The first process was the exclusion of articles based on titles and abstracts to remove in vitro and animal studies, commentary articles, and false retrievals. Details of the exclusion criteria are available in the published protocol [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…28 Collectively, with respect to the health impacts of active ecigarette use on CV health, several study findings display that even limited frequency and overall duration of e-cigarette use has been associated with increased heart rate and diastolic BP, as well as decreased oxygen saturation. 8,9 It should be noted, though, that while corroborating evidence from multiple investigations exists regarding the profound effects of e-cigarette use on BP and oxygen saturation, conflicting evidence currently exists on the effects regarding heart rate, stroke and/or coronary heart disease, particularly among longterm regular e-cigarette users. 29 Even so, large scale epidemiological findings arising from the U.S. National Health Interview Survey (n = 16,855) revealed that e-cigarette users, compared with non-users, remained in excess of 4-fold more likely to have a myocardial infarction (OR 4.09, 95% CI: 1.29-12.98).…”
Section: Cardiovascular Health Effects Related To Active E-cigarette Usementioning
confidence: 99%
“…7 While the etiological association between conventional tobacco smoking and cardiovascular (CV) diseases (CVD) is well established, to date insights regarding the potential long-term health impacts of e-cigarette use on CV health in adults remain conflicting, while in the young it remains to be elucidated. 8 The present review summarizes the current evidence regarding the health impacts of e-cigarette use on CV health in both adults and youth, elucidating its potential causal pathways and public health implications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation